2018
DOI: 10.3847/1538-4357/aab091
|View full text |Cite
|
Sign up to set email alerts
|

EUCLIA—Exploring the UV/Optical Continuum Lag in Active Galactic Nuclei. I. A Model without Light Echoing

Abstract: The tight inter-band correlation and the lag-wavelength relation among UV/optical continua of active galactic nuclei have been firmly established. They are usually understood within the widespread reprocessing scenario, however, the implied inter-band lags are generally too small. Furthermore, it is challenged by new evidences, such as the X-ray reprocessing yields too much high frequency UV/optical variations as well as it fails to reproduce the observed timescale-dependent color variations among Swift lightc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 110 publications
1
31
0
Order By: Relevance
“…As the intrinsic luminosity changes, the color would also change in response and is typically observed as being "bluerwhen-brighter" that has been widely found in quasar variabilities (e.g., Ruan et al 2014;Guo & Gu 2016), which could be well explained by the stochastic temperature fluctuation in an inhomogeneous accretion disk (e.g., Dexter & Agol 2011;Cai et al 2016Cai et al , 2018. Alternatively, the flux variability caused by variable extinction also displays a similar trend, since extinctions are more significant at shorter wavelengths (e.g., Calzetti et al 2000).…”
Section: Color Variabilitymentioning
confidence: 99%
“…As the intrinsic luminosity changes, the color would also change in response and is typically observed as being "bluerwhen-brighter" that has been widely found in quasar variabilities (e.g., Ruan et al 2014;Guo & Gu 2016), which could be well explained by the stochastic temperature fluctuation in an inhomogeneous accretion disk (e.g., Dexter & Agol 2011;Cai et al 2016Cai et al , 2018. Alternatively, the flux variability caused by variable extinction also displays a similar trend, since extinctions are more significant at shorter wavelengths (e.g., Calzetti et al 2000).…”
Section: Color Variabilitymentioning
confidence: 99%
“…The original model proposed by Dexter & Agol (2011) is able to match the disk size with micro-lensing observations but larger than thin disk theory prediction. More excitingly, the revised inhomogeneous disk models by Cai et al (2016Cai et al ( , 2018 can further explain the observed timescale dependent color variations, and inter-band coordinations/lags without light echoing.…”
Section: The Underlying Physicsmentioning
confidence: 91%
“…Theoretically, disc thermal fluctuating models (Dexter & Agol 2011;Cai et al 2016Cai et al , 2018Cai et al , 2019Cai et al , 2020 associate the multi-wavelength variability to magnetic turbulence in the accretion disc. Note such fluctuation models indeed predict bluer averaged EUV SEDs than the standard thin disk model without temperature fluctuation, and the stronger turbulence the bluer the mean SED (see Fig.…”
Section: Discussionmentioning
confidence: 99%